A subjective and objective comparison of tissue contrast and imaging artifacts present in routine spin echoes and in iterative decomposition of asymmetric spin echoes for soft tissue neck MRI. Issue 102 (May 2018) - Sarkar, Subhendra N.; Hackney, David B.; Greenman, Robert L.; Vachha, Behroze A.; Johnson, Emelia A.; Nagle, Sue; Moonis, Gul
Highlights: Image quality for fat suppressed FSE in neck regions is challenging due to large magnetic susceptibility variation. IDEAL FSE is insensitive to B0 and B1 inhomogeneities and preserves tissue contrast despite susceptibility challenges. High SNR in IDEAL translates into high CNR and consequently to higher image quality compared to routine FSE. IDEAL sequences produce less vascular pulsation artifacts for tissues adjacent to large neck vessels. Fat specific IDEAL images offer additional diagnostic information for fat deficient test lesions like oncocytoma. Abstract: Objective: FSE sequences play key roles in neck MRI despite the susceptibility issues in neck region. Iterative decomposition of asymmetric echoes (IDEAL, GE) is a promising method that separates fat and water images resulting in high SNR and improved fat suppression. We tested how neck tissue contrasts, image artifacts and fat separation as opposed to fat suppression in terms of image quality compare between routine and IDEAL FSE. Methods: IDEAL based and routine T1 and T2 -weighted FSE sequences were applied for neck MRI at 1.5T and 3T. Overall image quality including fat suppression, tissue contrast, image artifacts and lesion conspicuity were subjectively assessed for 20 patients clinically indicated for neck MRI. Quantitative tissue contrast estimates from parotid area were compared between IDEAL and routine FSE for 7 patients. Four patients with oncocytoma were also reviewed to assess benefits of separately reconstructed fat specific image sets. Results: Subjective tissue contrast and overall image quality including image sharpness, fat suppression and image artifacts were superior for IDEAL sequences. For oncocytoma fat specific IDEAL images provided additional information. Objective CNR estimates from a central slice were equivalent for IDEAL and routine FSE at both field strengths. Conclusions: We demonstrated that high SNR inherent in IDEAL FSE consistently translates into high tissue contrast with image quality advantages in neck anatomy where large susceptibility variation and physiological motions reduce image quality for conventional FSE T1 and T2 . However, the objective contrast estimates for parotid gland at isocenter were statistically equivalent for IDEAL and conventional FSE perhaps because at or near isocenter routine FSE works well. Additionally, fat specific IDEAL image sets add to diagnostic specificity for fat deficient lesions.